045 Effect of siponimod on cortical grey matter and thalamic volume in secondary progressive multiple sclerosis - Arnold, Douglas L; Fox, Robert J; Bar-Or, Amit; Cree, Bruce AC; Giovannoni, Gavin; Gold, Ralf; Vermersch, Pat- rick; Meier, Daniela Piani; Arnould, Sophie; Kappos, Ludwig (Journal of neurology, neurosurgery and psychiatry, 2022)
BackgroundGrey matter (GM) loss is associated with cognitive decline and physical disability in multiple sclerosis (MS). In Phase 3 EXPAND study, siponimod significantly reduced disability progression, cognitive decline and whole brain volume loss in patients with secondary progressive MS (SPMS).MethodsMagnetic resonance imaging (MRI) from EXPAND were pooled and analysed using high reso- lution T1 and conventional MRI. Analysis included intent-to-treat population (full analysis set, FAS) and per protocol set (PPS). Change from baseline in cortical grey matter (cGM) and thalamic volumes were assessed.ResultsIn the FAS, adjusted mean percent change in volume from baseline at M12 and M24, respectively, was −0.07 versus −0.59 (88% reduction vs placebo, p<0.0001) and −0.51 versus −0.90 (43% reduction; p<0.0001) for cGM; −0.54 versus −1.01 (47% reduction; p< 0.0001) and −1.20 versus −1.74 (31% reduction; p=0.0001) for the thalamus. PPS values were 0.01 versus −0.60 (100% reduction; p< 0.0001) and −0.39 versus−1.04 (63% reduction; p< 0.0001) for cGM; −0.47 vs −0.94 (50% reduction; p< 0.0001) and −1.02 versus −1.77 (42% reduction; p< 0.0001) for the thalamus.ConclusionsSiponimod significantly reduced cGM and thalamic volume loss compared with placebo in patients with SPMS.g.giovannoni@qmul.ac.uk